Pengaruh CAR, NPL, LDR dan NIM Terhadap Profitabilitas Perbankan (Studi Kasus Pada Bank Umum yang Terdaftar di BEI Tahun 2017-2019) - Sella Agustina Maharani; Afi Rahmat Slamet; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract The purpose of this research is to analyze the effect of CAR, NPL, LDR and NIM on profitability (ROA) to banking company that registered in BEI 2017-2019. The dependent variable of this research is profitability (ROA), while an independent variables are used Capital Adequancy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM). The population in this research are 45 banks that registered in the Indonesian Stock Exchange. Samples were obtained by purposive sampling method and selected 28 banks which fit the criteria.This research using multiple linear regression to obtain a picture of the relation between one variable and others. The result of this study indicate that CAR, NPL, LDR and NIM simultaneously have an affect to bank profitability (ROA). CAR and LDR does not have an effect o bank profitability (ROA), while NPL and NIM have an effect to bank profitability (ROA)            Key words: CAR (Capital Adequancy Ratio), NPL (Non Performin Loan), LDR (Loan to Deposit Ratio), NIM ( Net Interest Margin) and Profitability (ROA)